Antimicrobial resistance control efforts in Africa: a survey of the role of Civil Society Organisations - Jessica L. Fraser; Yewande H. Alimi; Jay K. Varma; Tracie Muraya; Tapiwanashe Kujinga; Vanessa K. Carter; Constance Schultsz; Victor J. Del Rio Vilas (Global Health Action)
Background: Antimicrobial resistance (AMR) is a growing public health threat in Africa. AMR prevention and control requires coordination across multiple sectors of government and civil society partners. Objectives: To assess the current role, needs, and capacities of CSOs working in AMR in Africa. Methods: We conducted an online survey of 35 CSOs working in 37 countries across Africa. The survey asked about priorities for AMR, current AMR-specific activities, monitoring practices, training needs, and preferences for sharing information on AMR. Further data were gathered on the main roles of the organisations, the length of time engaged in and budget spent on AMR-related activities, and their involvement in the development and implementation of National Action Plans (NAPs). Results were assessed against The Africa Centres for Disease Control and Prevention (Africa CDC) Framework for Antimicrobial Resistance (2018–2023). Results: CSOs with AMR-related activities are working in all four areas of Africa CDC’s Framework: improving surveillance, delaying emergence, limiting transmission, and mitigating harm from infections caused by AMR microorganisms. Engagement with the four objectives is mainly through advocacy, followed by accountability and service delivery. There were limited monitoring activities reported by CSOs, with only seven (20%) providing an example metric used to monitor their activities related to AMR, and 27 (80%) CSOs reporting having no AMR-related strategy. Half the CSOs reported engaging with the development and implementation of NAPs; however, only three CSOs are aligning their work with these national strategies. Conclusion: CSOs across Africa are supporting AMR prevention and control, however, there is potential for more engagement. Africa CDC and other government agencies should support the training of CSOs in strategies to control AMR. Tailored training programmes can build knowledge of AMR, capacity for monitoring processes, and facilitate further identification of CSOs’ contribution to the AMR Framework and alignment with NAPs and regional strategies.